ANALISIS PENERAPAN ORGANISASI PEMBELAJAR (LEARNING ORGANIZATION) DI PT FEDERAL INTERNATIONAL FINANCE (FIF) CENTRAL MALANG - Ellyn Eka Wahyu; Nilawati Fiernaningsih; Masreviastuti Masreviastuti; Liana Rokhawati (Politeknik Negeri Malang, 2019)
This research was aimed to determine whether PT FIF Central Malang has implemented the concept of Learning Organization to its full potential in achieving company goals. This type of research is a qualitative study with a questionnaire as a data collection tools. The sample of this research was 38 people using purposive sampling technique. Data analysis method uses data triangulation. The results showed positive and significant results, so based on the triangulation of data that had been done it could be explained that PT FIF Central Malang had applied the concept of a learning organization in achieving company goals. These results are in line with research conducted by several previous studies that the concept of learning organization could positively and significantly affected to the performance improvement of an organization.